Development of Survey Scales for Measuring Exposure and Behavioral Responses to Disruptive Intraoperative Behavior. Issue 7 (October 2021) - Villafranca, Alexander; Hamlin, Colin; Rodebaugh, Thomas L.; Robinson, Sandra; Jacobsohn, Eric
Abstract : Objectives: Disruptive intraoperative behavior has detrimental effects to clinicians, institutions, and patients. How clinicians respond to this behavior can either exacerbate or attenuate its effects. Previous investigations of disruptive behavior have used survey scales with significant limitations. The study objective was to develop appropriate scales to measure exposure a nd responses to disruptive behavior. Methods: We obtained ethics approval. The scales were developed in a sequence of steps. They were pretested using expert reviews, computational linguistic analysis, and cognitive interviews. The scales were then piloted on Canadian operating room clinicians. Factor analysis was applied to half of the data set for question reduction and grouping. Item response analysis and theoretical reviews ensured that important questions were not eliminated. Internal consistency was evaluated using Cronbach α. Model fit was examined on the second half of the data set using confirmatory factor analysis. Content validity of the final scales was re-evaluated. Consistency between observed relationships and theoretical predictions was assessed. Temporal stability was evaluated on a subsample of 38 respondents. Results: A total of 1433 and 746 clinicians completed the exposure and response scales, respectively. Content validity indices were excellent (exposure = 0.96, responses = 1.0). Internal consistency was good (exposure = 0.93, responses = 0.87). Correlations between the exposure scale and secondary measures were consistent with expectations based on theory. Temporal stability was acceptable (exposure = 0.77, responses = 0.73). Conclusions: We have developed scales measuring exposure and responses to disruptive behavior. They generate valid and reliable scores when surveying operating room clinicians, and they overcome the limitations of previous tools. These survey scales are freely available.